The effect of solution-focused approaches on adolescents' peer bullying skills: A quasi-experimental study - Ozturk Copur, Ebru; Kubilay, Gulumser (Wiley, 2022)
Purpose: To determine the effect of solution-focused approaches on adolescents' coping skills with peer bullying. Design and methods: A quasiexperimental design was used. The sample consisted of 68 adolescents. Using solution-focused approaches group were held with the intervention cohort. These were six sessions focused on improving participants' ability to cope with bullying. The data on the impact of the solution-focused approaches were collected using the Personal Information Form and the Adolescent Peer Relationship Instrument (APRI). Results: After the solution-focused approaches, the scores on components of the APRI (bullying and victimization) were significantly lower in the intervention group (p < .05). Practice Implications: A solution-focused group approach can be used by nurses to address the issue of peer bullying in schools.
Keywords: Solution-focused approach; bullying; nursing